Methodology of physical recreation: problems, experience, recommendations - V.P. Zaytsev; S.V. Manucharjan; Kr. Prusik; K. Prusik; M. Cieslicka; M. Szark-Eckardt (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The article contains methodical approaches in the process of conducting practical classes with the students on discipline «Physical recreation». The methodical reception is shown, also their definition, the importance of definitions during the life of the person, including the student. The essence of physical recreation in the understanding of students for passive and active recreation is uncover, as well as formulating the tasks in forming, recovering, strengthening and preserving the health of different age groups of the population. The methodological principles of physical recreation described in detail in the context of its performance by students. It uses traditional principal means for physical culture ((physical exercise, movement modes, natural factors, massage, occupational therapy, mechanotherapy). They are distinguished by various forms, methods, and activities, bearing recreational character.